Total elbow arthroplasty versus plate fixation for distal humeral fractures in elderly patients: a systematic review and meta-analysis. Issue 4 (July 2018) - Jordan, Robert W.; Saithna, Adnan; Kimani, Peter; Modi, Chetan; Drew, Stephen; Lawrence, Tom
Abstract : Background: Distal humeral fractures represent about 1% to 2% of adult fractures. Open reduction and internal fixation (ORIF) has traditionally been the standard treatment; however, fracture comminution and osteoporotic bone may prevent adequate fixation, and total elbow arthroplasty (TEA) is an alternative. The aim of this meta-analysis was to determine which procedure provided superior clinical outcomes for elderly patients with distal humeral fractures. Methods: A systematic review of the literature was conducted in accordance with the PRISMA guidelines. Cases series and comparative studies reporting functional outcomes or complications after TEA and ORIF in patients over 60 yr of age with an acute distal humeral fracture were included. The studies were appraised using validated quality assessment scales. Results were pooled from different studies using meta-analysis techniques, and the functional outcomes, complications, and frequency of revision surgery were compared. Results: The search strategy identified 27 studies: one randomized controlled trial, four comparative studies, 14 ORIF cases series, and eight TEA case series. TEA was associated with statistically significant and clinically superior Mayo Elbow Performance score (MEPS) and Disability of the Arm, Shoulder and Hand (DASH) scores when compared to ORIF in elderly patients while having a statistically significant lower complication rate. Conclusions: Meta-analysis of comparative studies demonstrated that TEA is associated with statistically significant and clinically superior MEPS and DASH scores when compared to ORIF in elderly patients.